Chronic Ethanol Consumption Impairs the Tactile-Evoked Long-Term Depression at Cerebellar Molecular Layer Interneuron-Purkinje Cell Synapses in vivo in Mice - Li, Da-Yong; Bing, Yan-Hua; Chu, Chun-Ping; Cui, Xun; Cui, Song-Biao; Qiu, De-Lai; Su, Li-Da (Frontiers in Cellular Neuroscience, 2019)
The cerebellum is sensitive to ethanol (EtOH) consumption. Chronic EtOH consumption impairs motor learning by modulating the cerebellar circuitry synaptic transmission and long-term plasticity. Under in vitro conditions, acute EtOH inhibits both parallel fiber (PF) and climbing fiber (CF) long-term depression (LTD). However, thus far it has not been investigated how chronic EtOH consumption affects sensory stimulation-evoked LTD at the molecular layer interneurons (MLIs) to the Purkinje cell (PC) synapses (MLI-PC LTD) in the cerebellar cortex of living animals. In this study, we investigated the effect of chronic EtOH consumption on facial stimulation-evoked MLI-PC LTD, using an electrophysiological technique as well as pharmacological methods, in urethane-anesthetized mice. Our results showed that facial stimulation induced MLI–PC LTD in the control mice, but it could not be induced in mice with chronic EtOH consumption (0.8 g/kg; 28 days). Blocking the cannabinoid type 1 (CB1) receptor activity with AM-251, prevented MLI-PC LTD in the control mice, but revealed a nitric oxide (NO)-dependent long-term potentiation (LTP) of MLI–PC synaptic transmission (MLI-PC LTP) in the EtOH consumption mice. Notably, with the application of a NO donor, S-nitroso-N-Acetyl-D, L-penicillamine (SNAP) alone prevented the induction of MLI–PC LTD, but a mixture of SNAP and AM-251 revealed an MLI-PC LTP in control mice. In contrast, inhibiting NO synthase (NOS) revealed the facial stimulation-induced MLI-PC LTD in EtOH consumption mice. These results indicate that long-term EtOH consumption can impair the sensory stimulation-induced MLI–PC LTD via the activation of a NO signaling pathway in the cerebellar cortex in vivo in mice. Our results suggest that the chronic EtOH exposure causes a deficit in the cerebellar motor learning function and may be involved in the impaired MLI–PC GABAergic synaptic plasticity.